2021
DOI: 10.1002/hep.31695
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of TLR8 Agonist GS‐9688 (Selgantolimod) in Chronic Hepatitis B: Remodeling of Antiviral and Regulatory Mediators

Abstract: BaCKgRoUND aND aIMS: GS-9688 (selgantolimod) is a toll-like receptor 8 agonist in clinical development for the treatment of chronic hepatitis B (CHB). Antiviral activity of GS-9688 has previously been evaluated in vitro in HBVinfected hepatocytes and in vivo in the woodchuck model of CHB. Here we evaluated the potential of GS-9688 to boost responses contributing to viral control and to modulate regulatory mediators.appRoaCH aND ReSUltS: We characterized the effect of GS-9688 on immune cell subsets in vitro in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 55 publications
1
65
0
Order By: Relevance
“…Reports have shown both functional ( 10 ) and defective TLR8 response ( 37 ) in CHB. However, in vitro testing of Selgantolimod showed comparable levels of cytokines in PBMC from healthy and CHB subjects ( 31 ). In clinical trial of this agonist in healthy subjects, we previously showed IL-12p40, IL-12p70, IL-1RA and IL-18 induction in serum ( 14 ), here we show T FH polarizing cytokines, IL-12 is induced with the agonist in monocytes from CHB patients which led to naïve CD4 + T cells to differentiated into CXCR5 + BCL-6 + ICOS + IL-21 + T FH .…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown both functional ( 10 ) and defective TLR8 response ( 37 ) in CHB. However, in vitro testing of Selgantolimod showed comparable levels of cytokines in PBMC from healthy and CHB subjects ( 31 ). In clinical trial of this agonist in healthy subjects, we previously showed IL-12p40, IL-12p70, IL-1RA and IL-18 induction in serum ( 14 ), here we show T FH polarizing cytokines, IL-12 is induced with the agonist in monocytes from CHB patients which led to naïve CD4 + T cells to differentiated into CXCR5 + BCL-6 + ICOS + IL-21 + T FH .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the frequency of Tfh cells might be used as a novel predictor for the prognosis of HBV-ACLF. In fact, a recent study showed that TLR8 agonist GS-9688 (selgantolimod) promoted Tfh differentiation and function by increasing the expression of ICOS, which may be able to activate antiviral effector function (22). Thus, we suppose Tfh cells may be a therapeutic target in those treatment-resistant HBV-ACLF patients through regulating the function of Tfh cells in the future.…”
Section: Discussionmentioning
confidence: 87%
“…In another study, GS-9688 was reported to exert anti-HBV effect in the woodchuck model of CHB [ 118 ], where it reduced viral loads over 5 logs and suppressed woodchuck hepatitis surface antigen (WHsAg) in 50% of the treated chronically infected woodchucks [ 118 ]. Another recent study also showed the therapeutic potential of GS-9688 in CHB, where GS-9688 induced cytokines in human PBMCs that could activate antiviral effector function by different immune mediators, including NK cells, HBV-specific CD8+ T cells, CD4+ follicular helper T cells, and mucosal-associated invariant T cells [ 119 ]. The anti-HBV activity of TLR9-ligand has been reported previously [ 120 , 121 ].…”
Section: Potential Of Tlr Agonists As Immunomodulatorsmentioning
confidence: 99%